Enhancing root canal filling homogeneity: Investigating cross linked and injection molded techniques against single cone method - Patel, Foram Hemantkumar; Mehta, Tarang Kirtibhai; Bhavsar, Keval Anilbhai; Attur, Kailash Madivalayya; Attur, Shylaja Kailash; Patel, Avani Bipinbhai (Journal of conservative dentistry, 2025)
Context: The most common cause for endodontic failures has been ascribed to improper obturation of root canal space. An ideal endodontic filling should approximate the obturation material in close contact with the root canal wall to minimize the sealer content. Voids cause a problem of harboring bacteria leading to treatment failure. Aims: The aim of the present study was to compare and analyze filled area after using single cone, cross-linked gutta-percha core-carrier systems, and injection-molded thermoplasticized obturation technique. Subjects and Methods: Thirty-nine human mandibular premolars with a single oval canal were selected. Biomechanical preparation was done using HyFlexCM. Samples were categorized into three groups and filled with single cone, cross-linked gutta-percha core-carrier systems, and injection-molded thermoplasticized obturation technique. Sectioning was done at 3, 6, 9, and 12 mm from the apex. The percentage of gutta-percha-filled areas (PGFAs) and percentage of void areas (PVA) were analyzed using a stereomicroscope. Statistical Analysis Used: Analysis of variance-one way. Results: A statistically significant difference was not found in terms of PGFA and PVA at 3 mm among the three groups. However, the cross-linked carrier-based and injection-molded thermoplasticized groups showed overall highly significant differences with the single-cone obturation group at 6, 9, and 12 mm (P < 0.001). Conclusions: The cross-linked carrier-based and injection-molded thermoplasticized groups exhibited more gutta-percha filled area than single-cone obturation technique and thus turned out to be more effective in achieving homogenous root canal filling.